Poligami di Indonesia dalam perspektif CEDAW dan mazhab Shafi’i - Qurrotul Ainiyah (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2017)
Convention on the Elimination of All Forms of Discrimination against Women or CEDAW’s paradigm ofthought is gender equality, women should be given rights as men in principles and rights in marriageincluding marriage approval, marriage dismissal, marriage guardian, and so on. Discrimination is anattitude that opposite of justice and must be eliminated. The source of the CEDAW’s concept paradigmof thought is mind, lustand feeling, and then the concept of CEDAW considered rational andMaslahah (good) enough. The Shafi’i paradigm is guiding the mind and heart based on religious texts.The religious prohibition have Madharat in the world and in the after life. If the world have not seen theMadharat, it will be feltin the after life. The Maslahah principle in CEDAW included al-Maslahah al-Mulghah, as it is contrary enough to the teachings of Islamic law contained in religious texts. In fact, anylaw that is contrary to Islamic law governed by religious texts is not Maslahah but Madharat and shouldbe abandoned even it is logical and good enough by the reason of thought. CEDAW uses Nash’sGuidelines that understand the Qur’an verse by considering Siyaq al-Kalam, so it interprets ‘fair’bythough of mindor in love and affection. Polygamy will no longer mu’asharah bi al-ma’ruf by causing thesuffering of wives. With the Sad al-Dhari’ah consideration, it will change the polygamy law from allowedor mubah to haram lighoirihi. Shafi’i madhhab uses the dalalah ‘ibarah’ which understands the Qur’anverse without considering siyaq al-kalam. The law of Haram li ghairihi on the permissibility of Polygamybased on Sad al-Dhari’ah is not applicable generally, and means that polygamy can not be judged as haramli ghairihi but keep see the conditions with the consideration of the single person condition.